ANALISIS EFEKTIVITAS KINERJA KARYAWAN PERUSAHAAN PEMBIAYAAN PT. ADIRA CABANG DENPASAR 1 BERDASARKAN PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA - Ni Wayan Cahya Ayu Pratami (UNHI Press, 2019)
Good human resource management in a company not only imposes leadership power on its employees, but how a leader can also wisely receive complaints or suggestions conveyed by his employees for the common good, so that employees feel at home and comfortable while working improving employee performance is through improvements in leadership and work environment. These improvements are expected to foster job satisfaction for employees. Increased job satisfaction is also expected to have an impact on increasing the performance of employees themselves. Leadership and work environment have an influence on job satisfaction and employee performance in the finance company PT. Adira Denpasar 1 Branch, involving a number of respondents. Respondent data will be processed using the Partial Least Square (PLS) method through the Smart PLS 2.0 M3 program. The results found that leadership has a positive impact on job satisfaction but the relationship does not have a significant effect while the work environment has a significant and positive influence on performance, and job satisfaction has a positive impact on performance but does not have a significant effect. The results of statistical tests that show no significance are caused by indicators of lack of leaders in carrying out their roles in carrying out their duties and ordering their employees to achieve goals.